Analisis laporan keuangan bank syariah indonesia dengan pendekatan rasio likuiditas - rahman, augie ryan; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to assess the financial performance of Bank Syariah Indonesia (BSI) over the past five years, focusing on two key indicators, namely the liquidity ratio and Capital Adequacy Ratio (CAR). The analysis was conducted based on BSI's annual financial reports and official publications from the Islamic banking authority for the period 2020–2024. The results of the study show that BSI's liquidity level is stable and consistent within limits that are considered healthy, as reflected in the FDR and Cash Ratio, which are able to offset the growth in financing and third-party funds. Meanwhile, the capital adequacy ratio (CAR) shows strengthening throughout the research period and is consistently well above the minimum regulatory requirements. These findings indicate that BSI has a solid liquidity structure and strong capital capacity to deal with financial risks and support financing expansion. Overall, this analysis confirms that BSI's performance in terms of liquidity and capital is at a very healthy level and is capable of supporting the long-term sustainability of Islamic banking operations.